Penerapan Model Discovery Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa SMK - Nugraha, Guruh; ., Sarkani; Supianti, In In (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2020)
Science growing in line with the technology expanding was found, needed to life skill to obtain manage and use the science to be used to necessary of life today and the is going the come. One of them is skill of mathematics. But in fact we are still find student who has the ability to think critical mathematics is low. One of alternatives learning that can improve the ability to think criticaly mathematically students used the learning model of Discovery Learning. This study attempts to knowing have increased capasity to think criticaly mathematical students through the model of Discovery Learning better than conventional learning model. the methods this research is experiment of research. The population of the research is all students in class XI SMKN 3 Bandung and this sample is students in class XI MM 1 and XI MM 2 at SMKN 3 Bandung. And instrument used in research is the result of the study. From this research obtain edcondution the ability to think criticaly mathematicaly student who obtain lessons learned Discovery Learning better than Conventional obtain lesson learned. Advice provided is it is hoped that teacher creating a favorable and involves student in learning so the student able to expanding mathematical think criticaly. Learning with a model Discovery Learning very good used in learning, that can be used as an alternative in learning activities.